Trophic niche size and overlap decreases with increasing ecosystem productivity. Issue 9 (22nd May 2020) - Lesser, Justin S.; James, W. Ryan; Stallings, Christopher D.; Wilson, Rachel M.; Nelson, James A.
Abstract : The production and transfer of biomass through trophic relationships is a core ecosystem function. The movement of energy through the food web is mediated by organisms operating in their niche space. For generalists, the size of this niche space is inherently plastic and changes in response to available food sources. Therefore, this relationship between ecosystem productivity and niche size is an important determinant of ecosystem function. Competing theories about the nature of this relationship predict that as productivity increases niche size will either increase as species capitalize on a general increase in resource availability or decrease as it becomes viable to focus on preferred production channels. Here, we test these two competing theoretical frameworks using a novel approach to determine trophic niche size using stable isotope analysis and hypervolume metrics. Resource use is quantified in two generalist fish species at three productivity levels in a seagrass ecosystem. Niche size of both species was inversely related to seagrass productivity, consistent with the hypothesis that increasing productivity allows species to focus on a narrower diet. This pattern describes the relationship between ecosystem production and niche size and provides an empirical ecological explanation for the resource maximization behaviors commonly observed in nature.